1990
DOI: 10.1111/j.1547-5069.1990.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualization of the Uncertainty in Illness Theory

Abstract: The theory of uncertainty in illness has its strongest support among subjects who are experiencing the acute phase of illness or are in a downward illness trajectory (mishel, 1988a). The theory has not addressed the experience of living with continual, constant uncertainty in either a chronic illness or in an illness with a treatable acute phase and possible eventual recurrence. Since uncertainty characterizes many, most prevalent, long-term illness conditions, there is a need to reconceptualize the theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
957
1
71

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 812 publications
(1,056 citation statements)
references
References 17 publications
27
957
1
71
Order By: Relevance
“…22 Mishel's theory of uncertainty in chronic illness 26 identified that transitions can bring personal or spiritual growth and result in a positive experience. Although an event may seem negative to a provider, the patient and or caregiver may experience new perspectives on life, death or existential reality.…”
Section: Discussionmentioning
confidence: 99%
“…22 Mishel's theory of uncertainty in chronic illness 26 identified that transitions can bring personal or spiritual growth and result in a positive experience. Although an event may seem negative to a provider, the patient and or caregiver may experience new perspectives on life, death or existential reality.…”
Section: Discussionmentioning
confidence: 99%
“…Illnessrelated uncertainty has been associated with psychological distress in a variety of patient populations (24,39,46) and with lower quality of life in RA patients (47). Fortunately, illness-related uncertainty is modifiable through the use of interventions such as educational strategies, assistance to the individual in changing his or her appraisal of uncertainty, availability of supportive health care providers, and strengthening of the individual's sources of social support (24,48).…”
Section: Discussionmentioning
confidence: 99%
“…Illness uncertainty -the inability to explain the cause of an illness, define an illness, or make predictions about future health 10,11 -can undermine health-related decision making and psychological adjustment. 12,13 Such barriers posed by illness uncertainty may increase patient motivation to learn more information from sequencing results.…”
Section: Introductionmentioning
confidence: 99%